The future of immunotherapy for sarcoma. (2nd August 2016) - Tsukahara, Tomohide; Emori, Makoto; Murata, Kenji; Mizushima, Emi; Shibayama, Yuji; Kubo, Terufumi; Kanaseki, Takayuki; Hirohashi, Yoshihiko; Yamashita, Toshihiko; Sato, Noriyuki; Torigoe, Toshihiko
ABSTRACT: Introduction : The use of immunotherapeutic challenges for sarcoma has a long history. Despite the existence of objective responses, immunotherapy has been overshadowed by the results of chemotherapy, especially for osteosarcoma. However, the prognosis for non-responders to chemotherapy is still poor and immunotherapy is now focused on again. Areas covered : We reviewed the following types of clinical trials of immunotherapy for sarcoma: (i) vaccination with autologous tumor cells, (ii) vaccination with peptides derived from tumor-associated antigens, (iii) adoptive cell transfer using engineered T cells expressing T cell receptor directed at NY-ESO-1 and (iv) immune checkpoint inhibitors targeting CTLA-4 and PD1/PDL1. Expert opinion : The immunogenicity of sarcoma might be lower than that of melanoma. Patients with small lesions who have not received any chemotherapy are good candidates for peptide-based immunotherapy. Combining peptide vaccination and immune checkpoint inhibitors is an attractive option, and long-lived memory T cells are attracting attention. Memory T stem cells defined by CD95+ are long-lived and have the capacity for self-renewal and multidifferentiation. We also identified a novel memory T cell population, young memory T cells defined by CD73+CXCR3+. Regulation of such memory T stem cells will be useful for peptide vaccination and adoptive cell transfer.